2020
DOI: 10.3389/fnins.2020.00409
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Provides Exceptional Accuracy to ECoG-Based Functional Language Mapping for Epilepsy Surgery

Abstract: The success of surgical resection in epilepsy patients depends on preserving functionally critical brain regions, while removing pathological tissues. Being the gold standard, electro-cortical stimulation mapping (ESM) helps surgeons in localizing the function of eloquent cortex through electrical stimulation of electrodes placed directly on the cortical brain surface. Due to the potential hazards of ESM, including increased risk of provoked seizures, electrocorticography based functional mapping (ECoG-FM) was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 57 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Ravi Prakash et al [ 135 ] introduced an algorithm based on DL for ECoG-based functional mapping (ECoG-FM) for eloquent language cortex identification. However, the success rate of ECoG-FM is low as compared with electro-cortical stimulation mapping (ESM).…”
Section: Non-eeg-based Epileptic Seizures Detectionmentioning
confidence: 99%
“…Ravi Prakash et al [ 135 ] introduced an algorithm based on DL for ECoG-based functional mapping (ECoG-FM) for eloquent language cortex identification. However, the success rate of ECoG-FM is low as compared with electro-cortical stimulation mapping (ESM).…”
Section: Non-eeg-based Epileptic Seizures Detectionmentioning
confidence: 99%
“…Some clinical sites record from the penetrating micro-electrodes, used in case a tissue with the implanted electrode is damaged, so such penetrating electrode “moves” and in result allows recording from areas with healthy tissue [ 5 ]. The ECoG is performed mainly on patients who will have to have a follow-up resection procedure for sure [ 241 , 242 ]. Figure 9 shows an example of the ECoG signal.…”
Section: Electrocorticographymentioning
confidence: 99%
“…The ECoG is used mainly to locate the epileptogenic zones during preliminary planning, mapping cortical functions, and prediction of the success of epileptic surgical resection. The ECoG, despite its invasiveness, has several advantages over alternative—non-invasive diagnostic methods [ 242 ]: Flexible placement of recording and stimulation electrodes; It can be performed at any stage before, during and after surgery; It allows direct electrical stimulation of the brain and identification of critical areas of the cortex, which must be avoided during surgery; It provides greater accuracy and sensitivity than the scalp EEG recordings, as the spatial resolution is higher and the signal-to-noise ratio is better due to closer proximity to the neural activity. …”
Section: Electrocorticographymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that accepting electrodes with a high response in either the gamma band, the beta band, or in both, as potentially eloquent yielded better results than using either band alone, especially in the language cortex. Likewise, machine- and deep- learning approaches ( Prakash et al, 2017 ; RaviPrakash et al, 2020 ) have shown that using the entire frequency spectrum, rather than only the gamma band, yields better mapping results, although it was not made clear which part of the spectrum offered the most additional information. In addition, while there is considerable heterogeneity in the task employed between studies, few studies have directly compared different tasks in the same group of patients.…”
Section: Introductionmentioning
confidence: 99%